2018
DOI: 10.1021/acsnano.7b08566
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characterization of Discrete Defects and Impact of Defect Density on Photoluminescence in Monolayer WS2

Abstract: Transition-metal dichalcogenides (TMDs) are an exciting class of 2D materials that exhibit many promising electronic and optoelectronic properties with potential for future device applications. The properties of TMDs are expected to be strongly influenced by a variety of defects which result from growth procedures and/or fabrication. Despite the importance of understanding defect-related phenomena, there remains a need for quantitative nanometer-scale characterization of defects over large areas in order to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
124
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 48 publications
13
124
2
Order By: Relevance
“…-domain (P circ ~ 40%) of our h-WS 2 samples even at RT, in stark contrast to recent reports by other groups (with P circ = 0.2% ~ 32%) on monolayer WS 2 , [40][41][42] as summarized in Table S2. The PL peak for both domains was found to slightly blue-shift to 1.96 eV at a lower temperature (LT) 80 K. As exemplified in Figure 3g, the LT (80 K) PL intensity of the   detection at the -domain increased threefold relative to the corresponding RT signals, whereas the PL intensity of the   detection remained the same at 80 K. In particular, the DOP at the -domain approached nearly 90% at 80 K. In contrast, the LT (80K) PL spectra at the -domain revealed that the PL intensities for both the   and   detections increased tenfold relative to the corresponding PL spectra at RT, as exemplified by Figure 3h.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…-domain (P circ ~ 40%) of our h-WS 2 samples even at RT, in stark contrast to recent reports by other groups (with P circ = 0.2% ~ 32%) on monolayer WS 2 , [40][41][42] as summarized in Table S2. The PL peak for both domains was found to slightly blue-shift to 1.96 eV at a lower temperature (LT) 80 K. As exemplified in Figure 3g, the LT (80 K) PL intensity of the   detection at the -domain increased threefold relative to the corresponding RT signals, whereas the PL intensity of the   detection remained the same at 80 K. In particular, the DOP at the -domain approached nearly 90% at 80 K. In contrast, the LT (80K) PL spectra at the -domain revealed that the PL intensities for both the   and   detections increased tenfold relative to the corresponding PL spectra at RT, as exemplified by Figure 3h.…”
Section: Resultscontrasting
confidence: 99%
“…To understand the correlation between the defect density and PL intensity, we followed a similar analysis by Rosenberger et al 42 Specifically, we assumed that the defect-related non-radiative recombination occurred when excitons collided with defects and resulted in non-radiative recombination. For an exciton with an effective collision radius r traveling with a speed v, an area swept by the exciton over a time period t in the 2D sheet with a defect density n d would result in N collisions, where N = n d (2rvt).…”
mentioning
confidence: 99%
“…These features have been observed for several TMDCs in both C-AFM and STM images. 29 , 33 , 40 , 66 They have been interpreted as metal-like defects and are induced by atom substitution/vacancy on the outermost TMDC layers. 33 A zoom-in between these defects shows a smooth and flat surface in both the topography and the current image (see Figure 2 b and its inset).…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30] Recent work counting individual defects using conductive AFM has demonstrated that this three-fold symmetric region has a higher defect density than surrounding areas of the single crystal. 56 Additionally, this three-fold symmetric region has previously been shown to be preferentially oxidized under high-power laser irradiation and suggests that it contains a higher density of defects. 26 The observation of increased defect density has not been limited to the threefold symmetric areas.…”
Section: Discussionmentioning
confidence: 97%